A creep model of pile-frozen soil interface considering damage effect and ice effect. (January 2022) - Gao, Qiang; Wen, Zhi; Zhou, Zhiwei; Brouchkov, Anatoli; Wang, Dayan; Shi, Rui
An important source of time-dependent pile deformation is creep behavior at pile-frozen soil interface in permafrost regions. A creep model for pile-frozen soil/ice interfaces was proposed based on a series of multistage creep tests. The test results show that the creep behavior of the pile-frozen soil/ice interfaces is easily observed at a steady rate larger than 0 even at a small load level, which increases as the increase of load level. The elastic shear modulus increases at a slowing down rate with the increase of load level. The interfaces are mainly strengthened during the creep process until the occurrence of the accelerating creep, which is more obvious for frozen soil. A large amount of ice in frozen soil can enhance the creep rate and reduce the carrying capacity of pile foundation. The viscosityη 2 reflecting steady creep rate, the instantaneous shear modulusG 0, and the critical stressτ S required for describing damage behaviors distribute in the form of Bigaussian asymmetric peak function with ice content. The Burger model considering ice effect and damage effect is feasible to describe the entire creep behavior of the interfaces. Sensitivity analysis reveals that ice content in frozen soil has a marked influence on pile deformation, a cooling method can probably adjust the creep deformation of pile in frozen soil with high ice content.